Enhancement Of Landfill Daily Cover Performance By Using Mixture Of Local Soil, Pressmud And Empty Fruit Bunch In Minimizing The Migration Of Heavy Metals In Landfill - Mohamad, Maheera (2018)
An increase of heavy metals concentration in landfill leachate is a concern as it is a major threat to human health and surrounding environment. Landfill daily soil cover amendment is a good option to reduce the mobility of heavy metals in the landfill cell. In this study, local soil samples were mixed with waste from sugar manufacturing process, pressmud and empty fruit bunch (EFB) of palm oil at different percentage of weight ratio. Then, batch adsorption experiments were performed to evaluate the effectiveness of soil mixtures in removing the heavy metals. Their performances were compared to the individual performance of the soil, pressmud and EFB. The physicochemical and geotechnical properties of the soil, pressmud, EFB and soil-pressmud-EFB mixtures characterization as well as leaching test were carried out. The leaching test method included batch equilibrium test and soil column test. From the characterization study, there were some improvements on the physicochemical and engineering properties of mixtures compared to soil alone. Batch equilibrium test showed that the soil-pressmud-EFB mixtures have the capability to remove more than 59% to 98.9% Cd, Cr, Cu, Fe, Mn, Ni and Zn metals from solution. Meanwhile, the removal efficiency of heavy metals from solution in the soil alone was ranged from 1.6% to 33.3%. Pressmud alone, however, showed 78.4% to 99.7% heavy metals removal while EFB indicated 19.9% to 56.2% removal. The response surface methodology (RSM) concerning Central Composite Design (CCD) was used to optimize the experimental condition in the removal of heavy metals. According to the results, initial concentration of 4.05 mg/L and 30 minutes contact time were required to effectively remove all heavy metals. Based on the characterization study, the removal efficiency and the column test, the soil-pressmud-EFB mixture particularly 50S:40P:10E was the most suitable combination and possessed great potential as daily cover to reduce heavy metals migration in landfill leachate.